2011
DOI: 10.1186/1471-2334-11-55
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of systemic immunoreactivity to Aggregatibacter actinomycetemcomitans leukotoxin in relation to the incidence of myocardial infarction

Abstract: BackgroundChronic infections and associated inflammatory markers are suggested risk factors for cardiovascular disease (CVD). The proinflammatory cytokine, interleukin (IL)-1β, is suggested to play a role in the regulation of local inflammatory responses in both CVD and periodontitis. The leukotoxin from the periodontal pathogen Aggregatibacter actinomycetemcomitans has recently been shown to cause abundant secretion of IL-1β from macrophages. The aim of the present study was to compare the prevalence of syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…The present study found slightly but significantly increased presence of Ltx‐neutralizing antibodies in patients versus controls. Significant correlation was found between presence of strong Ltx immunoreactivity with increasing age in examined patients and controls, which is in line with previous findings 13,17,34,35 . These findings are difficult to explain when the colonization pattern of A. actinomycetemcomitans is believed to be strictly vertical with a transmission window that closes early in life 1 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present study found slightly but significantly increased presence of Ltx‐neutralizing antibodies in patients versus controls. Significant correlation was found between presence of strong Ltx immunoreactivity with increasing age in examined patients and controls, which is in line with previous findings 13,17,34,35 . These findings are difficult to explain when the colonization pattern of A. actinomycetemcomitans is believed to be strictly vertical with a transmission window that closes early in life 1 .…”
Section: Discussionsupporting
confidence: 81%
“…A. actinomycetemcomitans is also considered to be an early colonizer owing to its ability to colonize buccal epithelial cells, which could act as reservoir for the bacterium 7 , 36 . However, transmission between adults may occur randomly, contributing to increased prevalence of Ltx antibodies related to higher age, as seen in previous studies 13,17,34,35 and in the present study.…”
Section: Discussionsupporting
confidence: 60%
“…However, the strong correlation between the presence of highly leukotoxic (JP2-clone) A. actinomycetemcomitans and development of attachment loss in adolescents indicates an important role of LtxA in the pathogenesis of aggressive periodontitis [ 3 ]. The treatment strategies of periodontal disease are today focused on the elimination of the bacteria in the subgingval biofilm by mechanical techniques or with antibacterial agents [ 87 ]. Therapeutic agents that target the cellular and molecular inflammatory host response might be a future treatment alternative for periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that systemic leukotoxin neutralization is correlated to the presence of this bacterium in the subgingival plaque (Källestål et al, 1991;Sjödin et al, 1995;Carlsson et al, 2006). The prevalence of systemic leukotoxin antibodies has been shown to be present in >50% in samples from adults and without significant differences in relation to periodontitis (Brage et al, 2011;Johansson et al, 2011). Interestingly, systemic leukotoxin neutralization correlates to decreased risk of the incidence of stroke in woman .…”
Section: Acquired Humoral Immune Response Against Leukotoxinmentioning
confidence: 99%